EFFECT OF E-PROCUREMENT PRACTICES ON SUPPLY CHAIN PERFORMANCE - Waithaka, Robert Kariuki; Kimani, John G. (Global Journal of Purchasing and Procurement Management, 2021)
Purpose: the purpose of the study is to establish the influence of electronic procurement practices on supply chain performance. Methodology: The researcher employed a method of reviewing desktop literature. To assess the feasibility of the subject for testing, three processing stages were applied on the subject under review. This was the first step of the original identification of all papers based on the effect of electronic sourcing activities on the efficiency of the supply chain. A second quest covered fully available literature on the issue of e-procurement processes and efficiency of the supply chain. The third stage included the collection of journals that were freely available. The researcher arrived at 12 papers that were relevant for review after an in-depth quest into the top key terms (e-procurement processes, supply chain management, performance). Findings: Procurement performance is the backbone of an organization success since it contributes to competitive purchase and acquisition of quality goods that puts the organization products or services in the competitive edge in the market. In the analysis of the use of e-procurement on performance of the procurement functions of county governments in Kenya, the results revealed that e-procurement is positively related with performance of supply chain function of County Governments in Kenya. Unique contribution to theory, practice and policy: The study therefore recommended that the Government come up with policies on adoption of e-procurement practices and provide critical resources and leadership in adoption of e-procurement. It is recommended that in order to achieve maximum benefits of reduced order processing time, reduced costs, reduced human errors and improved delivery, management should enhance electronic system and insist on all orders being processed electronically.